2022
DOI: 10.3390/cancers14236003
|View full text |Cite
|
Sign up to set email alerts
|

Resistin Promotes Nasopharyngeal Carcinoma Metastasis through TLR4-Mediated Activation of p38 MAPK/NF-κB Signaling Pathway

Abstract: NPC is a type of malignant tumor with a high risk of local invasion and early distant metastasis. Resistin is an inflammatory cytokine that is predominantly produced from the immunocytes in humans. Accumulating evidence has suggested a clinical association of circulating resistin with the risk of tumorigenesis and a relationship between blood resistin levels and the risk of cancer metastasis. In this study, we explored the blood levels and the role of resistin in NPC. High resistin levels in NPC patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…It has been reported that p38 MAPK pathway modulates varieties of important cellular physiological/pathological processes such as cell growth, differentiation, apoptosis, and inflammatory response [19,20]. Protein interaction network analysis revealed that the eukaryotic transcription factor NF-κB, which is involved in cellular functions such as inflammation, immune response, cell proliferation and apoptosis, interacted with the p38 protein [21]. Moreover, p38 MAPK acts upstream of the NF-κB signaling pathway in neuropsychiatric diseases [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that p38 MAPK pathway modulates varieties of important cellular physiological/pathological processes such as cell growth, differentiation, apoptosis, and inflammatory response [19,20]. Protein interaction network analysis revealed that the eukaryotic transcription factor NF-κB, which is involved in cellular functions such as inflammation, immune response, cell proliferation and apoptosis, interacted with the p38 protein [21]. Moreover, p38 MAPK acts upstream of the NF-κB signaling pathway in neuropsychiatric diseases [22].…”
Section: Introductionmentioning
confidence: 99%